SOSIALISASI TENTANG EVALUASI DRUG RELATED PROBLEMS (DRPS) ANTIBIOTIK PADA PASIEN PNEUMONIA RAWAT INAP ANAK RSUD DELI SERDANG - Cindy Monica; Aminah Syarifuddin (JURNAL PENGMAS KESTRA (JPK), 2021)
Infection is the most common disease in Indonesia, so antibiotic therapy is quite high. The increase in the use of antibiotics can lead to an increase in the irrational use of antibiotics. Irrational use can increase the number of bacteria resistance to antibiotics. Drung Related Problems (DRPs) that occur in the category of under-dose drugs (4.0%), and excess drug doses (2.0%) and no DRPs (94.0%). This indicates that the pharmacist's role is important in integrating patient therapy for the occurrence of DRPs.